2018
DOI: 10.1063/1.5054972
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive granular metal thin films of platinum–boron nitride and platinum–alumina at higher strain levels

Abstract: Granular metal thin films have a strain sensitivity much larger than continuous metal films. Experiments at high strain can help reveal their piezoresistive mechanisms. We deposit films of platinum nanoparticles in boron nitride (Pt:BN) as well as platinum particles in aluminum oxide (Pt:Al2O3) on polyimide foil as strain gauges. Under low strain of 0.1%, the films exhibit enhanced gauge factors, k=23 for Pt:BN and k=6 for Pt:Al2O3. Toward higher strain of 1.5%, Pt:BN shows reproducible and linear resistance-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition to the relative resistance change magnitude, consideration of resistance hysteresis is critical to produce reliable strain sensors. Piezoresistive strain sensors are usually associated with nonzero hysteresis [ 71 ] in their dynamic response to applied elastic strain and it is highly desirable to have as little hysteresis [ 72 ] as possible for practical applications. The first (plotted in red) and last (plotted in blue) representative strain hysteresis during the cyclic loading and unloading of each of the samples is shown in the corresponding subfigures (iii) in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the relative resistance change magnitude, consideration of resistance hysteresis is critical to produce reliable strain sensors. Piezoresistive strain sensors are usually associated with nonzero hysteresis [ 71 ] in their dynamic response to applied elastic strain and it is highly desirable to have as little hysteresis [ 72 ] as possible for practical applications. The first (plotted in red) and last (plotted in blue) representative strain hysteresis during the cyclic loading and unloading of each of the samples is shown in the corresponding subfigures (iii) in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The hysteresis observed in all the samples is less and comparable to those reported in the literature. [ 71,72 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GMs have been studied for >50 years [12,13] for both fundamental and applied research in nanoelectronics [14], plasmonics [15], superconductivity [16], and magnetism [17]. While GMs with various metals have been investigated, nearly all GM studies employed oxide-based insulators, such as SiO 2 , Al 2 O 3 , or yttria-stabilized zirconia (YSZ), with notable non-oxides including MgF 2 [18], BN [19], and carbon-based [20,21] GMs. Recently, we found that GMs with non-noble metals and oxide insulators form metal-oxides, which deleteriously increase GM conductivity at j < j c [5].…”
Section: Introductionmentioning
confidence: 99%